2017
DOI: 10.1002/term.2560
|View full text |Cite
|
Sign up to set email alerts
|

A co‐culture system with three different primary human cell populations reveals that biomaterials and MSC modulate macrophage‐driven fibroblast recruitment

Abstract: The biological response to implanted biomaterials is a complex and highly coordinated phenomenon involving many different cell types that interact within 3D microenvironments. Here, we increased the complexity of a 3D platform to include at least 3 cell types that play a role in the host response upon scaffold implantation. With this system, it was possible to address how immune responses triggered by 3D biomaterials mediate recruitment of stromal cells that promote tissue regeneration, mesenchymal stromal/ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…On the other hand, fibroblasts cultured in conditioned media derived from macrophages cultured on PTFE demonstrated significantly greater remodeling capacity, evidenced by increased collagen fibril deposition and organization within the hydrogel, compared to the other conditions . Lastly, Caires et al demonstrated the utility of a 3D coculture system to examine the interdependent effects of macrophages, fibroblasts, and MSCs on cell migration in response to poly(lactic acid) scaffolds or chitosan scaffolds . This model showed that macrophages cultured with chitosan scaffolds induced the greatest recruitment of fibroblasts (whether cocultured with MSCs or not) compared to natural killer cells, monocytes, or peripheral blood mononuclear cells cultured in the same fashion.…”
Section: Macrophage–fibroblast Crosstalk In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, fibroblasts cultured in conditioned media derived from macrophages cultured on PTFE demonstrated significantly greater remodeling capacity, evidenced by increased collagen fibril deposition and organization within the hydrogel, compared to the other conditions . Lastly, Caires et al demonstrated the utility of a 3D coculture system to examine the interdependent effects of macrophages, fibroblasts, and MSCs on cell migration in response to poly(lactic acid) scaffolds or chitosan scaffolds . This model showed that macrophages cultured with chitosan scaffolds induced the greatest recruitment of fibroblasts (whether cocultured with MSCs or not) compared to natural killer cells, monocytes, or peripheral blood mononuclear cells cultured in the same fashion.…”
Section: Macrophage–fibroblast Crosstalk In Vitromentioning
confidence: 99%
“…This model showed that macrophages cultured with chitosan scaffolds induced the greatest recruitment of fibroblasts (whether cocultured with MSCs or not) compared to natural killer cells, monocytes, or peripheral blood mononuclear cells cultured in the same fashion. Interestingly, if MSCs and macrophages were cocultured together, macrophages no longer recruited fibroblasts, suggesting that the arrival and signaling of MSCs may limit excessive fibroblast recruitment associated with fibrosis.…”
Section: Macrophage–fibroblast Crosstalk In Vitromentioning
confidence: 99%
“…It is becoming clear that it is necessary to have a deeper understanding of the interaction between MSCs and the host immune system after MSC implantation. Indeed, many studies have focused on the effects of MSCs on macrophages [ 13 15 ]; however, it is worth noting that macrophages are highly plastic and exist as different subtypes [ 16 ]. Therefore, it is essential to better understand the effects of MSCs on different subtypes of macrophages to provide solid theory as the basis for clinical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, polymer scaffold and perfusion-based 3D culture systems are used. 35,[50][51][52][53] MSCs can maintain the structural basis of cell-cell and cell-matrix contact by aggregation, thereby preventing cell loss due to apoptosis and improving implantation into host tissues. 54) Our experimental results show that MSCs in the 3D group express higher levels of ECM factors (e.g., CoL-I, fibronectin, and integrin), and more effectively resist IFN-γ-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%